Pengaruh variasi komposisi pada sifat magnet dari nanokomposit NiFe2O4/PANi yang disintesis dengan metode sol-gel spin coating (Composition variations effect on the magnetic properties of NiFe2O4 / PANi nanocomposites synthesized by the sol-gel spin coating) - - Helmita; - Ramli; - Hidayati (PILLAR OF PHYSICS, 2019)
NiFe2O4-polyaniline nanocomposites (NiFe2O4-PANi) with different contens of NiFe2O4 and PANi (30%,40%,50%,60% and 70% were prepared via sol-gel spincoating methode. The prepared sample were characterized using some teqniques such as X-Ray difraction and magnetic properties of the nanocomposites were measured using vibrating sample magnetometer. Nanocomposites were prepared using sol-gel spin coating technique (Fe(NO3)3.9H2O and Ni(NO3)2.6H2O precursors. Composite gels were coated on a glass substrate followed by drying and annealing to be used as thin films. Thin layers of nanocomposites were characterized using X-Ray Diffraction and Vibrating Sample Magnetometer, crystal size, coercivity, remanent magnetization, saturation magnetization at 30% composition were 44.36nm, 512Oe, 1.02mm, 1.02mm, at 40% variation respectively was 21.20 nm; 579,91Oe; 1,07 mm; 3,15mm; on 50% variation were 42,25nm; 562,42Oe; 1,04mm; 3,50mm; on 60% variation 43,96nm respectively; 639 .0Oe; 1.04mm; 3.01mm, at 60% variation respectively 39.18nm; 447.21Oe; 1.33mm; 4.38. Variations of NiFe2O4 / PaNi nanocomposite composition affect crystal size and magnetic properties of nanocomposite samples NiFe2O4 / PaNi